1992 ネン カキ グリーンランド カイ ノ スイオン ブンプ -LANCE ジョウセン ホウコク- - 牛尾, 収輝; ウシオ, シュウキ; 本田, 明治; ホンダ, メイジ; 伊藤, 一; イトウ, ハジメ; Ushio, Shuki; Honda, Meiji; Ito, Hajime (1994)
P(論文) 1992年8月17日から30日までの間, グリーンランド海における国際共同観測に参加した。ノルウェーの観測船R/V LANCEに同国のほか, ドイツ, イギリス, 米国, 日本から計5カ国17名の研究者が乗船し, 係留系の設置・回収, 採水, CTD観測などを実施した。日本側は水温観測を担当し, 流氷縁から東方の海域(77°～79°N, 3°W～15°E)2測線53点において水温の鉛直分布を測定した。流氷縁やスピッツベルゲン島近海では, 氷塊の融解や陸水の流入に起因すると考えられる複雑な水温構造が形成されていた。 Oceanographic observations in the Greenland Sea were conducted as a part of an international cooperative program. Seventeen scientists from five countries (Norway, Germany, England, U.S.A. and Japan) participated in the R/V LANCE cruise from August 17 to 30,1992. Mooring work, CTD measurements, water sampling and others were carried out both in the ice-covered and open sea. Temperature profiles from XBT casts were obtained at 53 points. The thermal structure of the eastern Greenland Sea seems to be strongly influenced by ice melting near the ice edge and land-water influx from Spitsbergen. departmental bulletin paper